Ominous skin lesion or benign sports-related imposter? - Pagliai Redbord, K.; Adams, B. B. (The Physician and Sportsmedicine, 2005)
Sports participants of all skill levels may develop sport-specific skin problems. Many skin disorders in athletes can mimic other potentially serious dermatologic entities that can be manifestations of musculoskeletal conditions, infections, inflammatory conditions, or carcinomas. Also, some skin conditions can alert the sports physician to look for possible anabolic steroid abuse. Physicians who are familiar with the relationship between the specific activities of various sports and skin disorders common to athletes will be able to properly diagnose, manage, and treat these conditions and educate players to prevent further injury.